Developmental biology - Gilbert, Scott F. (Massachusetts: Sinauer Associates, 2010)
During the past four years, the field of developmental biology has begun a new metamorphosis. The Ninth Edition of Developmental Biology mirrors this shift with a wholly revised text, over 600 new literature citations, and substantial reorganization of content. The introductory section has been streamlined from six chapters to three one each on developmental anatomy, the mechanisms of gene regulation during differentiation, and cell cell communication during morphogenesis. Another new feature is the addition of short part openers that address key concerns in developmental biology. These provide an introduction to the subsequent chapters, telling the reader what to expect and placing that information into a specific context. Each chapter ends with a guide to Web-based resources relevant to that chapter s content, and the Ninth Edition is the first to include a glossary of key terms. Some of the new material in this edition includes: mesenchymal and induced pluripotent stem cells; the transdifferentiation of pancreatic cells; new data on sea urchin micromere specification; the mechanisms whereby Sry and Wnt signaling determine mammalian sex; the memory of cell fate during amphibian limb regeneration; how bats got their wings and how dachshunds got their short legs.
Includes bibliographical references.; Glossary G1-G19p.; Index I1-I36p.
Keywords: Developmental biology; Embryology; Zoology